A short history of gardens - Campbell, Gordon (Oxford University Press, 2016)
Gardens, A Short History embraces the beauty and practicality of gardens, in history and culture across the world. Gordon Campbell also look at variations on the modern garden, including the suburban garden, the city garden, the guerrilla garden, and the vegetable garden, and considers the future of gardens.